2006
DOI: 10.1038/sj.jp.7211537
|View full text |Cite
|
Sign up to set email alerts
|

Association of preconceptional health care utilization and early initiation of prenatal care

Abstract: Objective: To assess whether women having preconceptional health care utilization were more likely to have early initiation of prenatal care than were women not having preconceptional health care utilization.Study Design: In this cohort study, data were collected prospectively from a population-based Perinatal Health Care Surveillance System in China. The analysis included 195 796 women who delivered single live births in 13 cities/counties during 1997 to 2000. Mantel-Haenszel test was employed to calculate ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
1
5
1
Order By: Relevance
“…The results of the study showed that women who received preconception care were more likely to have higher education. [ 11 18 ] In this context, our study is consistent with it. Justifying this conclusion, we can say that probably the increase in the level of female education led to a greater awareness of the importance of health services thus had more referrals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the study showed that women who received preconception care were more likely to have higher education. [ 11 18 ] In this context, our study is consistent with it. Justifying this conclusion, we can say that probably the increase in the level of female education led to a greater awareness of the importance of health services thus had more referrals.…”
Section: Discussionsupporting
confidence: 91%
“…In another study, in China, this rate has been reported to be 35.8%. [ 11 ] The prevalence observed in this study is more than the above case which is probably due to the differences in the research community. The results indicated that there is a wide gap between the received preconception care and the standard.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…2,23 This possibility is reinforced by evidence that utilization of PNC is associated with increased utilization of preconception care, infant care, and infant vaccination. [24][25][26] This "healthy adherer bias" was recently described through a meta-analysis showing that patients who adhere to drug therapy have lower all-cause mortality, even when that therapy is a placebo, suggesting that patient adherence may itself be a surrogate for health-promoting behaviors. 27 Adoption of PNC is likely multifactorial and can be predicted by factors such as having an unplanned pregnancy, late recognition of pregnancy, race, socioeconomic status, and geographic location.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to reduce the adverse pregnancy outcomes or improve the birth outcomes may need to start before pregnancy. Presently, preconception health care is strongly endorsed by the researchers and clinicians [17][19]. This study provides an overview of preconceptual screening examination service in rural areas of Hubei Province in 2012.…”
Section: Discussionmentioning
confidence: 99%